BEST PRACTICE INOVASI PEMBELAJARAN SEJARAH LOKAL MELALUI MEDIA POP UP BOOK DI KELAS IV SEKOLAH DASAR - Eem Sulaemah; Eem Sulaemah Sulaemah; Heri Maria Zulfiani; Insanul Qisti Bariyyah; Siti Nur Khasanah (STKIP Subang, 2025)
This study aims to describe the innovation of local history learning in Kulon Progo through pop-up book media in grade IV of elementary school. The research method used is descriptive qualitative, based on best practice, with a problem-based learning (PBL) and discovery learning approach. The subjects of this study consisted of 19 grade IV students of Margosari Elementary School, Kulon Progo. Data were collected through observation, project assessment, documentation of student work, learning motivation questionnaires, and statistical analysis using a paired sample t-test. The study's results showed an increase in students' average scores from 61.79 before treatment to 85.53 after using pop-up book media, with a significance of p < 0.001. In addition to improving learning outcomes, students showed increased motivation, creativity, and collaborative skills. Pop-up book media succeeded in making history learning more interesting, meaningful, and in accordance with the characteristics of elementary school students' cognitive development. This innovation supports the implementation of the Merdeka Curriculum, which emphasizes real-life experience-based learning and projects. The results of this study recommend the development of similar creative media in other subjects to improve the quality of learning at the elementary school level.